Translation Shift in English into Indonesian Subtitle of Guzaarish Movie - Tira Nur Fitria (Universitas Sanata Dharma, 2020)
This research aims to find out the types of shift and to know the most dominant type of shifts found in the English to Indonesian subtitle of “Guzaarish” movie. The method used in this research is qualitative research. The analysis shows that there are two types of translation shifts in the Guzarish movie subtitle. The translation shift is related to the various ways of an expression in the source text has been translated into the target text. The type of shifts found is both level and category shift as 242 data. The level shift shows 93 data or 38.43 %. The level shift occurs when an SL item has equivalent in a TL translation at the different linguistic levels of its own such as grammatical or lexical. The category shift shows total data 149 data or 61.57 %. Category shift is related to departures from formal correspondence in translation. The category shift consists of several types, they are structure shift as 80 data or 33.06 %, intra-system shift as 61 data or 25.21 %, rank/unit shift as 7 data or 2.89 %, and class shift as only 1 data or 0.41 %. It shows that the most dominant type of shift in “Guzaarish” movie subtitle is the category shift, especially the structure shift. It usually occurs at all levels. It is indicated by a situation when there are two different languages that have a different structural element.